Enforcement of Competition Law by the Indonesian Competition Commission in the Digital Market: Penegakan Hukum Persaingan Usaha oleh Komisi Persaingan Usaha Indonesia di Pasar Digital - Anhar, Nur Alifiah; Daga, Pelipus Benitus; Imelda, Lie Diana (Indonesian Journal of Law and Economics Review, 2026)
General Background: Business competition law plays a central role in maintaining market efficiency, innovation, and consumer welfare within the digital economy. Specific Background: In Indonesia, the Indonesian Competition Commission (KPPU) is authorized under Law No. 5/1999 to supervise and adjudicate unfair business competition practices, including cases in digital platform markets. Knowledge Gap: Despite extensive authority, the consistency and legal certainty of KPPU decisions in digital competition cases remain contested, particularly when judicial review overturns administrative rulings. Aims: This study examines competition law enforcement by KPPU through Decision No. 13/KPPU-I/2019 involving Grab Indonesia in the online transportation sector. Results: Using a normative legal approach with decision and regulatory analysis, the study found that KPPU’s enforcement capacity has not operated optimally due to legal uncertainty, inconsistent standards of proof, and procedural obstacles during judicial review. The findings also demonstrate that digital market characteristics, including network effects and platform-based business models, complicate the application of conventional competition law principles. Novelty: This study provides a focused legal evaluation of KPPU enforcement practices in Indonesia’s digital transportation market by linking procedural disputes with substantive competition law issues in the digital economy context. Implications: The study recommends harmonizing standards of proof and strengthening legal certainty to improve competition law enforcement and regulatory adaptation in Indonesia’s rapidly evolving digital market environment. Highlights: Judicial review created inconsistencies in digital market competition rulings. Procedural barriers limited regulatory authority in platform-based cases. Network-driven market structures complicated application of Law No. 5/1999. Keywords: KPPU, Enforcement Effectiveness, Law No. 5/1999, Business Competition, Online Transportation, Decision Analysis.